PENGAMBILAN TANAH SECARA PAKSA DI BAWAH AKTA PENGAMBILAN TANAH 1960: GANGGUAN KEPADA PERKARA 13 PERLEMBAGAAN PERSEKUTUAN? - Zakaria, Zalina (Jurnal Syariah, 2006)
In Malaysia, compulsory acquisition land by state authority is provided in the Land Acquisation Act 1960(Act 486). The Act actually was promulgated under Article 13 of the Federal Constitution which provides protective assurance against deprivation of property. It requires that the acqusation must be done in accordance with law and with adequate compensation given to the land owner.